Kecemasan Menghadapi Berakhirnya Masa Kontrak Kerja Pada Karyawan Kontrak PT. Intecon Bangun Persada Jember - Ali, Annisa Hummatul Maula (Psychospiritual: Journal of Trends in Islamic Psychological Research, 2023)
Feelings of worry, restlessness, anxiety, and unease are common symptoms of anxiety. The anxiety felt by contract employees is fear if the work contract that has been agreed between the company and the employee ends. Worries about their survival make contract employees feel anxious. This research aims to determine the factors that make contract employees feel anxious when facing the end of their work contract at PT. Intecon Bangun Persada. To find out the form of anxiety experienced by contract employees who are facing the end of their employment contract at PT. Intecon Bangun Persada. To find out efforts to overcome the various anxieties experienced by contract employees following the end of their employment contracts at PT. Intecon Bangun Persada Jember. This research uses a descriptive qualitative approach. The data collection techniques used semi-structured interviews, observation and documentation. The research subjects were four employees who were facing the end of their employment contracts at PT. Intecon Bangun Persada. Data analysis uses data reduction, data presentation, and giving a conclusion. The results of this research show that there are factors that influence the emergence of feelings of anxiety in contract employees when facing the end of their work contract, namely worry about losing the facilities they obtained while still working, including income (salary), allowances and opportunities. Meanwhile, contract employees have experienced conditions such as heart palpitations, dizziness, anxiety, and sweating when remembering that their work contract will end, and behavior such as avoiding causes of anxiety, depending on other people, and lack of self-confidence and excessive worry. Efforts to overcome this include exercising or just playing games, shopping, and other favorite activities.